Puzzle [videorecording (DVD)] - Macdonald, Kelly, 1976-; Khan, Irrfan, 1967-2020-; Denman, David, 1973- (Sony Pictures Home Entertainment, 2018)
A closely observed portrait of Agnes, who has reached her early 40s without ever venturing far from home, family or the tight-knit immigrant community in which she was raised by her widowed father. That begins to change in a quietly dramatic fashion when Agnes receives a jigsaw puzzle as a birthday gift and experiences the heady thrill of not only doing something she enjoys, but being very, very good at it.